A critical archaeology of cosmopolitan thinking return to the interwar years - Meyer, Daniel 1971-; Raulet, Gérard 1949-; Duncker & Humblot (Beiträge zur politischen Wissenschaft, 2023)
In the period between World Wars, the shock of World War 1 and the trauma caused by the conditions of the peace treaties generated an abundance of works on cosmopolitism and supranationalism. In the very period that witnessed the rise of nationalisms, pacifism and cosmopolitan thinking underwent a thorough renewal. While the Socialist International, bolstered by the progress of the Bolshevik revolution, claimed to offer an alternative to the weakness of Western democracies, these experienced a readjustment in the issues linked to cosmopolitanism, fuelled by the leading intellectual theories. Practically all the schools of thought and all the major intellectual figures played a part in this. Important turning points in theory were achieved. This enquiry into the intermediate period between both World Wars aims at outlining an archaeology of models and paradigms in contemporary cosmopolitan thought.